2020
DOI: 10.1002/cbdv.201900561
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Diversity and Pharmacological Properties of Rhus coriaria

Abstract: Rhus coriaria L. (Anacardiaceae), sumac, is a common condiment, appetizer and souring agent in the Mediterranean region that has a long history in traditional medicine. R. coriaria has been prescribed for the treatment of many ailments including diarrhea, ulcer, hemorrhoids, hemorrhage, wound healing, hematemesis, and eye ailments like ophthalmia and conjunctivitis. The plant is also used as diuresis, antimicrobial, abortifacient and as a stomach tonic. Sumac is known to be rich in different classes of phytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…Only EO-5 showed good percentages of β-caryophyllene (10.1%) and cembrene (8.4%) followed by palmitic acid (9.4%) and carvone (9.1%). It is also well reported that the β-caroyophyllene, cembrene, n-nonanal, and p-anisaldehyde were the major compounds too [28], but not in our samples.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Only EO-5 showed good percentages of β-caryophyllene (10.1%) and cembrene (8.4%) followed by palmitic acid (9.4%) and carvone (9.1%). It is also well reported that the β-caroyophyllene, cembrene, n-nonanal, and p-anisaldehyde were the major compounds too [28], but not in our samples.…”
Section: Resultssupporting
confidence: 68%
“…The mean IC 50 values of samples (1-8) were 175.2, 310.5, 169.5, 221.5, 165.5, 195.0, 225.0, and 165.5 µg/mL respectively, which were compared with the standard antioxidant rutin (IC 50 2.93 µg/mL). The potential antioxidant activity exhibited by the essential oil may be due to the presence of a variety of chemical compounds like β-caryophyllene [36,37], (E)-cinnamaldehyde [38], carvacrol [39], carvone [40], cembrene [41], eugenol [42], methyl palmitate, palmitic acid, oleic acid [28,43], α-copaene [44], α-himachalene [45], α-humulene [46], α-terpineol [47], and δ-cadinene [48] which are present in the these samples. All these compounds are collectively responsible for antioxidant activity.…”
Section: The Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro antibacterial activity of R. coriaria extracts has been previously suggested to be due to the presence of tannins (30). While some of the compounds identi ed in R. coriaria had been reported in the literature (3,5,6,7,16,17) and were in the reaxys.com database, we identi ed the presence of the compound quercetin diglucoside (C 27 H 30 O 17 ) in R. coriaria for the rst time. The other major compounds found were: quercitrin, myricetin glucoside, myricetin rhamnoside, ethyl gallate, ethyl digallate, thea avin, and baccatune.…”
Section: Discussionmentioning
confidence: 82%
“…Those studies found terpenoids, avonoids and hydrolysable tannins as possible active compounds (4,7,9,16). R. coriaria has a number of medicinal effects, exhibiting antidiabetic, anti-in ammatory, anticancer, antioxidant, antiviral, anti-ischemic, hypolipidemic and antibacterial activities (3,5,17). The antibacterial activity of R. coriaria was discovered using different fruit extracts: methanolic, ethanolic and water.…”
Section: Introductionmentioning
confidence: 99%